LA PRUEBA DE LA CAFEINA EN LOS ENFERMOS ULCEROSOS - VILLARREAL, P R (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
Expts using caffeine as a stimulant for gastric secretion in 8 acute cases of duodenal and 2 of gastric ulcer without previous prolonged more than 90 min and the free HC1 was maintained at a high level These patients treated until completely asymptomat
BOL INST ESTUD MED BIOL
Keywords: PRUEBA, CAFEINA, ENFERMOS, ULCEROSOS; CIENCIAS MEDICAS; FARMACODINAMICA; ACCION DE LOS MEDICAMENTOS